Teacher Perspective: Managing Students’ Behavior Problem in Teaching English at Primary School - Humaeroah Humaeroah; Ahmed Sardi; Ermawati Ermawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research is aimed to discover about students’ behaviors problem that teacher faced in language classroom that may occur in language teaching and learning process at primary schools. The objectives of the research are to find out how to  manage students’ behaviors problem at primary schools, especially in EFL classroom. This research used a descriptive qualitative research design. This research took ten English teachers in primary school as the participants of the research which were been taken through purposive sampling. The data of this research was collected by interview and audio recorder. The research findings show seven category of managing students behavior problem applied by the teachers in the English classroom , they are: positive relationships are developed and maintained between teacher and students, seating arrangement, encourage active learning, encourage experience-based learning, applying ICT in learning, support and strategy, the last is giving punishment. The ability of teachers to organise and manage classroom behaviours of their students is critical to achieving the learning objectives. Although behavioural management does not guarantee effective teaching, it makes improvement possible.